A state-of-the-art review and guidelines for tumor treating fields treatment planning and patient follow-up in glioblastoma. (January 2017) - Trusheim, John; Dunbar, Erin; Battiste, James; Iwamoto, Fabio; Mohile, Nimish; Damek, Denise; Bota, Daniela A; Connelly, Jennifer
Tumor treating fields (TTFields) are an integral treatment modality in the management of glioblastoma and extend overall survival when combined with maintenance temozolomide in newly diagnosed patients. Complexities exist regarding correct selection of imaging sequences with which to perform TTFields treatment planning. Guidelines are warranted first, to facilitate treatment planning standardization across medical disciplines and institutions, to ensure optimal TTFields delivery to the tumor and peritumoral brain zone while maximizing patient safety, and also to mitigate the risk of premature cessation of a potentially beneficial treatment. This summary guideline outlines methods for starting patients on TTFields, for monitoring patient response to therapy and provides a framework for evaluating when therapy should be re-planned, based on the extent of sequential imaging changes.